Cell-free activation of neutrophil NADPH oxidase by a phosphatidic acid-regulated protein kinase. - McPhail, L C (1995)
The phosphorylation-dependent mechanisms regulating activation of the human neutrophil respiratory-burst enzyme, NADPH oxidase, have not been elucidated. We have shown that phosphatidic acid (PA) and diacylglycerol (DG), products of phospholipase activation, synergize to activate NADPH oxidase in a cell-free system. We now report that activation by PA plus DG involves protein kinase activity, unlike other cell-free system activators. NADPH oxidase activation by PA plus DG is reduced approximately 70% by several protein kinase inhibitors [1-(5-isoquinolinesulfonyl)piperazine, staurosporine, GF-109203X]. Similarly, depletion of ATP by dialysis reduces PA plus DG-mediated NADPH oxidase activation by approximately 70%. Addition of ATP, but not a nonhydrolyzable ATP analog, to the dialyzed system restores activation levels to normal. In contrast, these treatments have little effect on NADPH oxidase activation by arachidonic acid or SDS plus DG. PA plus DG induces the phosphorylation of a number of endogenous proteins. Phosphorylation is largely mediated by PA, not DG. A predominant substrate is p47-phox, a phosphoprotein component of NADPH oxidase. Phosphorylation of p47-phox precedes activation of NADPH oxidase and is markedly reduced by the protein kinase inhibitors. In contrast, arachidonic acid alone or SDS plus DG is a poor activator of protein phosphorylation in the cell-free system. Thus, PA induces activation of one or more protein kinases that regulate NADPH oxidase activation in a cell-free system. This cell-free system will be useful for identifying a functionally important PA-activated protein kinase(s) and for dissecting the phosphorylation-dependent mechanisms responsible for NADPH oxidase activation.